The effect of incubation time on capacitation and acrosome reaction of in vitro ovine spermatozoa - J Wattimena (Jurnal Ilmu Ternak dan Veteriner, 2006)
The aim of this research was to know the effect of incubation time on capacitation and acrosome reaction of in vitro ovine spermatozoa. Twelve ejaculates from two Garut sheep were collected using artificial vagina and then evaluated macro and microscopically. After semen washing (centrifugation method), semen was diluted in Brackett and Oliphant (BO) medium and then incubated during 6 hours in incubator CO2, temperature 38.5ºC. Evaluation of capacitation and acrosome reaction was conducted on 0 hour, 0.5 hour, 1 hour, 2 hours, 4 hours and 6 hours incubation time. The result showed that incubation time had significant (P<0.05) effect on no capacitation sperm (pattern F), capacitation (pattern B) nad acrosome reaction (pattern AR). Incubation time had significantly (P<0.01) effect on subjective motility, life sperm and membrane integrity. Key Words: Ovine spermatozoa, incubation, capacitation, reaction, in vitro